Pemanfaatan Smartphone Bagi Petani Sebagai Alat Pengukur pH Tanah di Desa Tanggalrejo Mojoagung Jombang - Mohamad Nasirudin; Zulfikar Zulfikar; Anton Muhibuddin; Salim Ashar; Izzatul Indana; Ari Viqri Zakaria; Siti Aminah; Khusnul Mei Sintia (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
Technology in agriculture is something that cannot be separated from its application in the agricultural sector. The use of smartphones in soil pH measuring devices makes the measurement process faster, easier and more affordable. This research aims to develop a simple and affordable soil pH measuring tool for use by farmers in Tanggalrejo Village, Mojoagung, Jombang. The method approach taken for community service in Tanggalrejo Village is to use the Participatory Action Research (PAR) method. One of them is by implementing training methods and approaches from local farmers so that indirectly farmers in Tanggalrejo Village can capture the material well. This tool is named "Soil pH Meter" and is designed to help farmers manage the quality of their soil. This research involves the steps of designing, prototyping, field testing, and evaluation. This tool has the potential to increase efficiency in farming and help farmers take appropriate actions to increase crop yields. Based on the results of this community service activity, it can provide an overview of the use of a pH meter for accurate and efficient soil pH monitoring by: (1) Providing understanding and practice in checking soil pH using a telegram monitoring pH meter to farmers in Tanggalrejo Village, so that the Farmers know the condition of bass or acid soil and can determine good and correct handling. (2) Provide understanding and explanation about the use of smartphones, that the soil pH monitoring tool via telegram can be checked via smartphones used by farmers in Tanggalrejo Village.